2018
DOI: 10.3847/1538-4357/aab898
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Production of Extreme-ultraviolet Late-phase Solar Flares Using the Model Enthalpy-based Thermal Evolution of Loops

Abstract: Recent observations in extreme-ultraviolet (EUV) wavelengths reveal an EUV late phase in some solar flares that is characterized by a second peak in warm coronal emissions (∼ 3 MK) several tens of minutes to a few hours after the soft X-ray (SXR) peak. Using the model enthalpy-based thermal evolution of loops (EBTEL), in this paper we numerically probe the production of EUV late-phase solar flares. Starting from two main mechanisms of producing the EUV late phase, i.e., long-lasting cooling and secondary heati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This kind of confined flares has been extensively studied and the strength of the overlying field is thought to be an important factor determining whether a flare is confined (Cheng et al 2011;Nindos et al 2012;Liu et al 2016a;Amari et al 2018). In the event on 2012 July 04, the formations of secondary flare ribbons and late-phase flare loops (Figures 13 and 15) both suggest that the large-scale constraining fields overlying the erupting flux rope are partially reconnected (Sun et al 2013;Dai & Ding 2018). However, the remaining constraining fields that are not reconnecting still hold a high flux ratio compared to the flux rope, hence inhibit the eruption of the flux rope.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of confined flares has been extensively studied and the strength of the overlying field is thought to be an important factor determining whether a flare is confined (Cheng et al 2011;Nindos et al 2012;Liu et al 2016a;Amari et al 2018). In the event on 2012 July 04, the formations of secondary flare ribbons and late-phase flare loops (Figures 13 and 15) both suggest that the large-scale constraining fields overlying the erupting flux rope are partially reconnected (Sun et al 2013;Dai & Ding 2018). However, the remaining constraining fields that are not reconnecting still hold a high flux ratio compared to the flux rope, hence inhibit the eruption of the flux rope.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results clearly indicate that, at least for nanoflares, the decay timescales for plasma sampled in cooler SDO/AIA imaging bands are smaller than those found in the hotter channels. Theoretical work is still required to address the specific roles of conductive and radiative cooling in post-flare plasma (e.g., Cargill et al 1995;Dai & Ding 2018), particularly in a regime dominated by small-scale nanoflare events. An important outcome of this work is the fact that a smaller power-law index of ᾱ94 = 1.85 ± 0.02 is estimated for the SDO/AIA 94 Å time series, when compared to ᾱ171 = 1.89±0.01 for the co-spatial and co-temporal 171 Å observations.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the main flaring loops are significantly shorter (2L∼10-25 Mm), and hence evolve more quickly. In a numerical experiment using the EBTEL model, Dai & Ding (2018) found that with a strong initial loop heating, the hot and warm coronal emissions peak in the conductive cooling and radiative cooling stages, respectively. For the hot coronal emissions, the main flare peak and the late-phase peak temporally overlap because the cooling rate in all loops is very fast during the conductive cooling phase.…”
Section: Discussionmentioning
confidence: 99%
“…By using the model called enthalpy-based thermal evolution of loops (EBTEL; Klimchuk et al 2008;Cargill et al 2012; Barnes et al 2016), Li et al (2014) and Dai & Ding (2018) numerically probed the produc-tion of EUV late-phase flares. In particular, Dai & Ding (2018) found that even with an equal energy partition between the late-phase loop and main flaring loop, the warm coronal late-phase peak is still significantly lower than the corresponding main flare peak. This result may offer a clue as to why EUV late-phase flares are rare among all solar flares.…”
mentioning
confidence: 99%